Surface texture and fractal analysis of cemented carbide cutting tools - Ţălu, Ştefan; Kulesza, Slawomir; Bramowicz, Miroslaw; Zhuyu, Li (Microscopy research and technique, 2022)
This work highlights the usefulness of multi‐scale‐fractal and surface‐texture analysis in the machining of cemented carbide cutting edge by electrolytic‐abrasive honing (EAH) process. In order to achieve this, a fresh (untreated) cutting edge sample and the same sample after machining by electrolytic‐abrasive honing (treated) were studied upon their characteristics of surface texture and material properties to provide manufacturers a sustainable advantage in strengthening their tools. The surface characteristics of untreated and honed samples have been analyzed by evaluating four similar locations in the regions of each sample. Scanning electron microscopy (SEM) has been used for the characterization of materials surface. It was found that the unprepared cutting edge and the electrolytic‐abrasive sharp surface regions of the samples could be distinguished by area scale analysis and surface texture characteristics. The present study will help in improving the life span estimation of the tools and highlight the opportunities for the statistical modeling of lubrication mechanisms between the tool and the workpiece. The 3‐D surface micromorphology of cemented carbide cutting tools manufactured by electro‐abrasive honing was determined. The 3‐D surface microanalysis of the samples was performed using a scanning electron microscope. The surface texture characteristics and the fractal dimension of samples were determined. The surface texture directions of analyzed samples are shown in Cartesian graphs.